إجراءات التحري في جرائم المعلوماتية: دراسة تقويمية - يوسف محمد نور, د. خديجة (Gezira Journal of Economic and Social Sciences; مجلد 10 عدد 1 (2019), 2022)
جاءت هذه الدراسة بعنوان إجراءات التحري في جرائم المعلوماتية. وتنبع أهمية الدراسة من أن موضوع إجراءات التحري في جرائم المعلوماتية من المواضيع الجديدة والمهمة جداً، التي تحتاج إلى فقه يتعامل معها وقانون ينظمها. فهو يعد من المقدمات الضرورية التي تظهر مدى كفاءة الدول في التعامل مع تكنولوجيا المعلومات ومدى تواصلها مع معادلة التطوير والتطبيق على السواء. واستخدمت منهج الدراسة الاسلوب الوصفي التحليلي والاستنباطي استعرضت الباحثة في دراستها الموسومة بإجراءات التحري في جرائم المعلوماتية مفهوم جرائم المعلوماتية من تعريف جرائم المعلوماتية، وأنواعها وخصائصها. وتناولت فتح الدعوى الجنائية والتحري في جرائم المعلوماتية وذلك بفتح الدعوى الجنائية، ماهية التحري، وإجراءات التحري في جرائم المعلوماتية. وتوصلت الدراسة إلى أن هناك قصوراً في الكثير من التشريعات الجنائية الإجرائية في مواجهة جرائم المعلوماتية، وجود عدة صعوبات تكتنف إجراءات الجريمة المعلوماتية، منها التكاليف العالية التي تكتنف عمليات التحري عبر الإنترنت. وأوصت  بضرورة قيام المشرّع السوداني بوضع تشريع خاص لمكافحة مثل هذه الجرائم يبين فيه الإجراءات الخاصة لمتابعة وتحري ومحاكمة المرتكبين، محاولة التنسيق مع الجهات والهيئات الدولية لإصدار تشريعات موحدة تكفل إمكانية تتبع بعض أنواع الجرائم وخاصة التي تمس بأمن الدولة. Procedures for investigating information crimes: An Assessment Abstract        This study entitled the procedures of investigation in the informatics crimes, the significance of the study appear that the subject of investigation procedures in the informatics crimes is from the newest and important subjects that need to a jurisprudence deal with it and a law organize it, it is considered from the necessary introductions that demonstrate to what extent the state can deal with the informatics technology and tow what extent it can communicate with the application and development equation as equally. The study used the descriptive, analytic, inductive method, the researcher presented investigation procedures in the informatics crime by defining the informatics crimes, its types and specifications. The study presented the opening of the criminal claim and investigation in the informatics crime; therefore by opening the criminal claim, what is investigations, and the procedures in the Informatics crime. The study revealed that, there is a shortage in many of the procedural criminal legislations in encountering the informatics crime, existing of many obstacles embarrassed the procedures of the informatics crime, such as the high cost of the investigations processes via internet. The study recommends the Sudanese legislative by stating a special legislation to combat such these crimes, clarifying with it the allocated procedures to follow, investigate and sentencing the incurred, state security crimes